"Cerita Anak Nusantara" E-Book to Enhance an Understanding of Social Value in Early Childhood - Jojor Renta Maranatha; Asep Kurnia Jayadinata; Gia Nikawanti (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
The purpose of this study was to determine the effect of the e-book application "Cerita Anak Nusantara" as a learning media on the development of social values of early childhood. Â The study included aquasi-experimental control-group pretestâ€“posttest and was conducted in Purwakarta, Indonesia. Participants in this study were children aged 5-6 years, totaling 40 people. Data collection was carried out using a rating scale of social values of early childhood. This data was then analyzed using a paired sample t-test to determine the effect of learning media on the social values of early childhood, and an independent sample t-test to assess the difference in understanding of social values between the experimental group and the control group. The results of this study are: (1) There is an effect of the e-book learning media "Cerita Anak Nusantara" on the understanding of early childhood values. (2) There is a difference in the understanding of social values of early childhood children who received learning with the e-book media "Cerita Anak Nusantara" and early childhood children who received learning with conventional storybook media. It was concluded that the e-book media "Cerita Anak Nusantara" was more effective than conventional storybook media in increasing the understanding of social values in early childhood.